Religious involvement and right-wing authoritarianism in university students from Lima - Abanto Cerna, Fernando André (2025)
The aim of the study was to establish the relationship between religious involvement and right-wing authoritarianism (RWA), specifically, with its two dimensions. The sample consisted of 220 university students from the Faculty of Psychology at a public university in Lima. Data collection utilized the Duke University Religion Index (DUREL), developed by Koenig et al. (1997), and the Abbreviated Right-Wing Authoritarianism Scale by Zakrisson (2005), adapted by Cárdenas and Parra (2010). Prior to pursuing the objective, the psychometric properties of the instruments were analyzed, yielding adequate values in the DUREL in terms of its validity (Robust CFI = .998; Robust TLI = .995; Robust RMSEA = .071; SRMR = .061) and reliability (Ω = .864). In the case of RWA, it was chosen to work with the two-dimensional version, which showed acceptable values in its validity (51.65 % explained variance; λ > .40) and reliability (Ω > .60). The results revealed a statistically significant and direct association, of medium effect size, between religious involvement and the authoritarian aggression-submission dimension (p = .005 < .01; β = .32). However, contrary to expectations, it was found that there was no statistically significant association between religious involvement and the conventionalism dimension (p = .098 > .05). In conclusion, these findings provide evidence that religious involvement is related to authoritarian attitudes linked to submission and aggression toward those perceived as a threat to the social order, but not necessarily to rigid adherence to conventional social norms.